Ghavimi and Textualism - Hassan Zokhtareh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Studying some of Mahvash Ghavimi’s works in the academic and general area shows that she attaches significant importance to textual approaches. Contrary to many books that only explain the theories, Ghavimi in her three books, Sher No Dar Bouteh Naghd (Modern Poetry Criticism), Ava and Elgha (Sound and Suggestion), and Gozari Bar Dastan Nevisi (A study on Writing a story), after introducing Russian Formalism and French Structuralism to readers, in order to prove their effectiveness in literary research, uses them in examining and analyzing different types of Persian literature texts. This study tries to explore the origins and consequences of this approach in addition to Ghavimi’s method of using a textual approaches in the analysis of Persian texts. Although Ghavimi acts correctly in her analysis of Persian poems and novels with the help of textual approaches, she sometimes ignores its fundamentals, such as avoid judging and evaluating, as well as avoiding nationalism in the study of literature. Her emotional bond to the contextual approach, both in theory and in practice, is so profound that she cannot measure it accurately.